An audit on the diagnosis of primary CNS lymphoma. (15th October 2021) - Joe, Dorothy; Yin, Lucia; Kassam, Shireen; Cikurel, Katia; Lavrador, Jose-Pedro; Vergani, Francesco; Gullan, Richard; Bhangoo, Ranjeev; Ashkan, Keyoumars; Finnerty, Gerald
Abstract: Aims: Primary central nervous system lymphoma (PCNSL) is a rare form of non–Hodgkin lymphoma with exclusive manifestations in the central nervous system, leptomeninges and eyes. It forms around 5% of all primary brain tumours. It is an aggressive tumour which has a poor prognosis if left untreated. It is imperative that diagnosis is made timely so treatment can be started promptly. Therefore, we performed an audit looking into the speed of diagnostic process of PCNSL in our tertiary Neuro–oncology Unit. Method: Single-centre retrospective review of PCNSL cases referred to a tertiary Neuro–Oncology Unit over a six month period from June to November 2020. Results: A total of 1309 cases were discussed in the Neuro–oncology MDT meeting over the study period. Fourteen cases (6 male, 8 female; median age [range] 66 [59–83] years) were identified as highly likely PCNSL. Neuroimaging suggested PCNSL as the likely diagnosis in twelve patients. Twelve patients were started on steroids after CT or MRI brain scans. Nine patients had a surgical target and proceeded to have diagnostic brain biopsy. Two patients had different working diagnoses and three patients were deemed unsuitable for brain surgery. One patient required repeat brain biopsy. A tissue diagnosis was made in twelve patients. One patient deteriorated rapidly and one patient had a brain lesion that was deemed too high risk for surgery. The median time between neuroimaging and biopsy was 25 days. The median time taken from first investigation to the pathological confirmation of PCNSL was 36 days (range 6–86 days). Conclusion: The chief reason for delay in diagnosis of PCNSL was that patients were started on steroids before diagnostic investigations were completed. Steroids caused the brain lesions to become smaller or disappear. Accordingly, time was needed to allow withdrawal of steroids before diagnostic investigations could be repeated. Diagnostic delays may have been exacerbated by logistical issues associated with COVID–19. We propose that there needs to be greater awareness of how early introduction of steroids can markedly delay the diagnosis of PCNSL.